Mast Cells as Regulators of T Cell Responses - Bulfone-Paus, Silvia; Bahri, Rajia (Frontiers in Immunology, 2015)
Mast cells are recognized to participate in the regulation of innate and adaptive immune responses. Owing to their strategic location at the host-environment interface they control tissue homeostasis and are key cells for starting early host defence against intruders. Upon degranulation induced, e.g. by immunoglobulin E (IgE) and allergen-mediated engagement of the high-affinity IgE receptor, complement or certain neuropeptide receptors, mast cells release a wide variety of preformed and newly synthesized products including proteases, lipid mediators, and many cytokines, chemokines, and growth factors. Interestingly, increasing evidence suggests a regulatory role for mast cells in inflammatory diseases via the regulation of T cell activities. Furthermore, rather than only serving as effector cells, mast cells are now recognized to induce T cell activation, recruitment, proliferation and cytokine secretion in an antigen-dependent manner and to impact on regulatory T cells. This review synthesizes recent developments in mast cell-T cell interactions, discusses their biological and clinical relevance, and explores recent controversies in this field of mast cell research.